A Metabolic Activity Recovery of the Intestinal Microbiota in the Patients with Bronchial Asthma. (19th September 2022) - Ozimek, Mariusz; Ivashkin, Vladimir; Zolnikova, Oksana; Potskherashvili, Nino; Ivashkin, Konstantin; Dzhakhaya, Natiya; Kurbatova, Anastasia; Kryuchkova, Kira; Zaborova, Victoria
Abstract : Goals . We assessed the possibilities of correcting the short-chain fatty acids (SCFA) content and profiles in feces of patients with bronchial asthma. Background . It was established that the high biological diversity of intestinal microorganisms promotes the needed SCFAs production, which induces immune regulatory pathways and contributes to the anti-inflammatory response. Study . A group of 30 patients with allergic bronchial asthma (BA) were investigated in our study. All of the patients were tested for the presence of SIBO by the SCFA spectrum determination. For the SIBO treatment, 10 patients from the studied group were prescribed Rifaximinum with the 200 mg dose at 3 times a day for a week; the other 10 patients were prescribed Rifaximinum at the same dose, followed by the administration of the Lactobalance probiotic in capsules at 3 times a day for a month. A month probiotic course was assigned to the remaining 10 patients without SIBO, as part of the BA complex therapy. The SCFA studies were immediately carried out for all of the patients after the 1 month probiotic therapy course. Results . A normalization of the SCFA spectrum and anaerobic index for all of the studied patients were noted. Upon taking the probiotics, it was revealed in the patients without SIBO that the total content of fatty acids (p < 0.001 ), acetic and butyric acid (p < 0.001 ) had increased. The Rifaximinum course, followed by administration of the probiotics led to a decrease of the relative amount of isoacids and ratio of isoacids/acids in the studied patients as compared to the patients who had received Rifaximinum for the SIBO treatment only (p < 0.05 ). Conclusion . The obtained results demonstrate a potential opportunity of the drug influence on the active bacterial metabolites composition and amount in the intestinal biotope; as it was confirmed by the restoration of the intestinal microbiocenosis and microorganism habitat.